Fractionation and extraction of bio-oil for production of greener fuel and value-added chemicals: Recent advances and future prospects - Chan, Y.H. (Elsevier B.V., 2020)
Bio-oil is a highly valuable product derived from biomass pyrolysis which could be used in various downstream applications upon appropriate upgrading and refining. Extraction and fractionation are two promising methods to upgrade bio-oil by separating the complex mixture of bio-oil compounds into distinct fine chemicals and fractions enriched in certain classes of chemical compounds. In this review, various extraction techniques for bio-oil (organic solvent extraction, water extraction, supercritical fluid extraction, distillation, adsorption, chromatography, membrane, electrosorption and ionic liquid extraction), their associated features (extraction mechanisms involved, advantages and disadvantages), the characteristics of bio-oil extracts and their applications are presented and critically discussed. It was revealed that the most promising technique is via organic solvent extraction. Furthermore, the technological gaps and bottlenecks for each separation techniques are disclosed, as well as the overall challenges and future prospects of oil palm biomass-based bio-oil value chain. This review aims to provide key insights on bio-oil upgrading via extraction and fractionation, and a proposed way forward via technology integration in establishing a sustainable palm oil mill-based biorefinery. Â© 2020 Elsevier B.V.